An investigation into how Grade 10 Physical Sciences learners make sense of resultant vectors - Motsilili, Tshepo Elliot (Rhodes University, Faculty of Education, Department of Education, 2016)
The focus of this study was on how Grade 10 Physical Sciences learners make sense of resultant vectors. During my experience over more than 10 years as a Science teacher in Matatiele in the Eastern Cape Province I found that Grade 10 Physical Sciences learners consistently struggled to work with resultant vectors. Many studies have shown that learners in similar contexts are generally not doing well in Science. An interpretive paradigm was used in this study, focusing on the individual or a specific group in a qualitative case study approach and a social constructivist perspective. The unit of analysis was on how Grade 10 Physical Sciences learners make sense of resultant vectors. A diagnostic test, observation and videotaped lessons, learners' workbooks, summative test and stimulated recall interviews were used to gather data. The data were analysed inductively using a thematic approach and in relation to the main research question: How do Grade 10 Physical Sciences learners make sense of resultant vectors? The data were validated through watching the videotaped lessons with the teacher who had been observed teaching vectors. Also, transcripts of the interviews and a summary of discussions were given back to the teacher whose learners had been observed to verify the learners' responses and check for any misconceptions. It was found that linking scientific concepts to learners' prior knowledge enabled them to learn in a relaxed and non-threatening environment. In doing so, sense making of resultant vectors was possible. The study thus recommends that teachers should be supported in their endeavours to help learners make sense of scientific concepts during teaching and learning situations. Some language related challenges that were also encountered warrant further research.
Keywords: Uncatalogued